Status of food insecurity and its determinants by smallholder farmers in Shashogo district, Hadiya zone, Central Ethiopia - Tamrat Lolaso; Engdawork Assef; Teshale Woldeamanuel (Cogent Food & Agriculture)
Food insecurity happens in both developing and developed countries. This paper addresses spatial and temporal patterns of food insecurity and its determinants factors. The study used explanatory and descriptive research methods. This data was originated from household survey of 229 respondents who were interviewed during March and April 2022. Households self-report result shows that 52 (22.7%) of the respondents were food secure and 177 (77.3%) were food insecure. Estimated household food insecurity access via household food insecurity access scale showed that 82.1% was uncertain on food supply whereas having preferences of the type of and insufficient feeds variety food was 86%, which means 14% of respondents’ feed sufficient variety and preferences food. The proportion of respondents’ foods that are not wanted and eating a limited variety of food was reported 83% this resulted due to inability to eat preferred food. In general, 77.33% of respondents were food insecure, which described based on food insecure scale 28.8% mildly, 25.1% moderately and 23.3% severely. Season of food in/security was identified corresponding food insecure season from mid of September to December 6 (3.2%), from beginning of January up to April 34(18.4%), and from first May to end of August 144 (78.3%) which shows food security is good during the harvesting season and declined its security level. The spatial trend of the food security problem was reviewed in different agro-ecology zone. 35% of mid highland and 65% of low land were reported as food insecure. Policy makers would strengthen the existing coping and adaptation strategies.